2012
DOI: 10.1007/s11269-012-9998-z
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the Impact of Pricing Policies on Residential Water Demand: A Southern France Case Study

Abstract: The case study conducted in this paper looks at residential water pricing from three different points of view. It first describes existing urban water-pricing practices in Southern France, emphasizing that pricing is not yet being used as a tool for providing economic incentives to save water. It then looks at the observed impact of pricing on water consumption, through an econometric analysis of a cross-sectional data set. The analysis suggests that demand, with an estimated price elasticity of -0.2, is not y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 19 publications
1
27
0
1
Order By: Relevance
“…According to [33], Spanish water tariffs do not encourage water saving because the fixed fee is too high, the variable fee is not sufficiently progressive, and marginal prices are too low. For example, the 2006 French Water law requires that the fixed charges should not exceed 40% of the water bill for urban municipalities [34].…”
Section: The Reform Of the Sanitation Feementioning
confidence: 99%
“…According to [33], Spanish water tariffs do not encourage water saving because the fixed fee is too high, the variable fee is not sufficiently progressive, and marginal prices are too low. For example, the 2006 French Water law requires that the fixed charges should not exceed 40% of the water bill for urban municipalities [34].…”
Section: The Reform Of the Sanitation Feementioning
confidence: 99%
“…Total water losses during distribution vary greatly between countries, but, for example, Bulgaria, Greece, Malta, Ireland and the UK all show losses higher than the European average of 7.7 % (EUROSTAT, 2013). Water pricing is increasingly being used to try to improve water use efficiency (Bithas, 2008), although the resulting impacts on the residential sector seem to be rather limited compared to those in the agricultural sector (Rinaudo et al, 2012;Höglund, 1999). In addition, we should see improvements in water use efficiency especially in regions currently experiencing water scarcity due to the greater necessity of limiting overall water use.…”
Section: Discussionmentioning
confidence: 99%
“…The climate indicators usually considered in Table 1 include rainfall (annual or in the summer, number of rainy or dry days) and temperature (maximal or average). For France and Spain, it is found that water use increases with temperature (i.e., [12,17,19,22,23]) or with the number of dry days (i.e., [17]). On the contrary, water consumption decreases with rainfall levels (i.e., [18,19,24]).…”
Section: Residential Water Demand In France and Spain: A Brief Reviewmentioning
confidence: 99%
“…The impact of the seasonal population on household water consumption has already been investigated in the existing literature. In France and Spain, it is usually found that the seasonal population tends to contribute to an increase per capita water consumption (i.e., [13,17,24]). This positive effect may capture the larger share of recreational water use (swimming pool, garden watering) in holiday homes.…”
Section: Residential Water Demand In France and Spain: A Brief Reviewmentioning
confidence: 99%